2016
DOI: 10.2166/wst.2016.088
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic digestion of aliphatic polyesters

Abstract: Anaerobic processes for the treatment of plastic materials waste represent versatile and effective approach in environmental protection and solid waste management. In this work, anaerobic biodegradability of model aliphatic polyesters, poly(L-lactic acid) (PLA), and poly(ɛ-caprolactone) (PCL), in the form of powder and melt-pressed films with varying molar mass, was studied. Biogas production was explored in batch laboratory trials at 55 ± 1°C under a nitrogen atmosphere. The inoculum used was thermophilic dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The CH4(g) conversion of PLA under thermophilic conditions was more effective than under mesophilic conditions. A high level of biodegradation of 82% to 90% was reported in a mean digestion time of 90 days, [14], [96], [97], [98], [99]. Other authors have found a lower level of biodegradation, between 40 and 60%, with a similar timeframe for the digestion, [18], [81], [84], [100].…”
Section: Results For Pla Biodegradable Plastics Under Thermophilic Co...mentioning
confidence: 93%
See 1 more Smart Citation
“…The CH4(g) conversion of PLA under thermophilic conditions was more effective than under mesophilic conditions. A high level of biodegradation of 82% to 90% was reported in a mean digestion time of 90 days, [14], [96], [97], [98], [99]. Other authors have found a lower level of biodegradation, between 40 and 60%, with a similar timeframe for the digestion, [18], [81], [84], [100].…”
Section: Results For Pla Biodegradable Plastics Under Thermophilic Co...mentioning
confidence: 93%
“…However, it should be noted that the biodegradation levels were presented to 60% and 40%, respectively, were not the final biodegradation levels, as the BMP tests were stopped before they reached the plateau of methane production, [81], [84]. A decrease in the molecular weight of PLA was had a positive effect on the biodegradation kinetics, [98]. Thermophilic degradation of rigid pieces of PLA (1 x 1, 2 x 2, and 3 x 3 cm) assessed and observed negligible CH4(g) production of approximately 10 to 30 L CH4 / kg VS, [15].…”
Section: Results For Pla Biodegradable Plastics Under Thermophilic Co...mentioning
confidence: 99%
“…Pre-incubation of the inoculum with 20 mL of sludge acclimated to PLA 100 3 biogas x [ 101 ] PBS PBS 1 mm sheet 58 I/S = 2.85 (VS basis); working volume = 300 mL 100 0 0 CH 4 x [ 95 ] PCL PCL (Mn 58.1 kg.mol −1 ) 10 × 10 × 0.7 mm film 55 Plastic to inoculum ratio: 0.38 g COD/g VSS. Inoculum: thermophilic digested sludge from a digester 140 663 60 biogas DSC, SEM [ 160 ] …”
Section: Table A1mentioning
confidence: 99%
“… 75 --- 60.0 SEM x [ 159 ] PLA PLA (Mn 44.5 kg/mol) 10 × 10 × 0.7 mm film 55 Plastic to inoculum ratio: 0.15 g COD/g VSS. Inoculum: thermophilic digested sludge from a digester 120 677 74 biogas DSC, SEM [ 160 ] PLA PLA (Mn 3.4 kg/mol) Powder 55 Plastic to inoculum ratio: 0.15 g COD/g VSS. Inoculum: thermophilic digested sludge from a digester 90 520 56 biogas DSC, SEM PLA PLA (Mn 0.35 kg/mol) …”
Section: Table A1mentioning
confidence: 99%